Species : new interdisciplinary essays - Wilson, Robert A. (Robert Andrew) (MIT Press, 1999)
This fresh collection of essays, drawn from a broad range of disciplines, brings neglected cognitive, anthropological, and historical dimensions to philosophical debates over species.
"A Bradford book."
Keywords: Species -- Philosophy.; Espèces (Biologie) -- Philosophie.; SCIENCE -- Life Sciences -- Evolution.; Species -- Philosophy; Art; Biologie; Naturwissenschaften; Philosophie; Aufsatzsammlung; Soorten (biologie); Filosofische aspecten.; Ecology.; Earth & Environmental Sciences.; Espèces (biologie)